2003
DOI: 10.1021/tx0340910
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of Nilutamide by NO Synthases:  Implications for the Adverse Effects of This Nitroaromatic Antiandrogen Drug

Abstract: Nitric oxide synthases (NOSs) are flavohemeproteins that catalyze the oxidation of l-arginine to l-citrulline with formation of the widespread signal molecule NO. Beside their fundamental role in NO biosynthesis, these enzymes are also involved in the formation of reactive oxygen species and in the interactions with some xenobiotic compounds. Nilutamide is a nonsteroidal antiandrogen that behaves as a competitive antagonist of the androgen receptors and is proposed in the treatment of metastatic prostatic carc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 44 publications
0
29
0
Order By: Relevance
“…For example, it has been shown that recombinant neuronal NOS reduced nilutamide to the corresponding hydroxylamine via the formation of a nitroanion radical. This reaction was inhibited by molecular oxygen and a flavin/ NADPH binding inhibitor and stimulated by Ca 2+ /calmodulin, providing strong evidence that NOS was involved [26,28]. One of the underlying reasons for this non-classical reaction of NOS is that NOS has a reductase domain, which shares close homology with CYP reductase [29].…”
Section: Nitric Oxide Synthase (Nos)mentioning
confidence: 96%
See 3 more Smart Citations
“…For example, it has been shown that recombinant neuronal NOS reduced nilutamide to the corresponding hydroxylamine via the formation of a nitroanion radical. This reaction was inhibited by molecular oxygen and a flavin/ NADPH binding inhibitor and stimulated by Ca 2+ /calmodulin, providing strong evidence that NOS was involved [26,28]. One of the underlying reasons for this non-classical reaction of NOS is that NOS has a reductase domain, which shares close homology with CYP reductase [29].…”
Section: Nitric Oxide Synthase (Nos)mentioning
confidence: 96%
“…Recently NOS has been implicated in the nitroreduction of nitroarenes [26]. NOSes are flavohemoproteins that catalyze the oxidation of L-arginine to L-citrulline resulting in the formation of nitric oxide.…”
Section: Nitric Oxide Synthase (Nos)mentioning
confidence: 99%
See 2 more Smart Citations
“…However, the one-electron reductases in human tumour cells are poorly characterized. The diflavin reductase POR (NADPH:cytochrome P450 oxidoreductase) is considered to be a major contributor [16,19], but other flavoproteins have been shown to be capable of catalysing one-electron reduction of nitro compounds, including MTRR (methionine synthase reductase), NDOR1 (NADPH-dependent diflavin oxidoreductase 1) [16], NOS (nitric oxide synthase) isoforms NOS1, NOS2A and NOS2B [20,21], thioredoxin reductase [22], CYB5R3 (NADHdependent cytochrome b 5 reductase 3) [23], aldehyde oxidase [24,25] and xanthine oxidase [26,27]. However, there is little information on the contribution that these or other enzymes make, at physiological levels of expression, to bioreductive prodrug activation in tumours.…”
Section: Introductionmentioning
confidence: 99%